Investigating the Impact of Nursing Technician-Led Mindfulness Interventions on Postoperative Pain Management and Opioid Use: A Qualitative Study - Amsha Mohammad Farraj Alsuhali,; Asma Dhabyan Maseer Alanazi,; Tahani Fahad Dabshi Alshammari,; Habibah Maseer M Aldhafeeri,; Najah Mohammed Jarwan Alanazi,; Wafaa Zewayed Dlimy Alanazi,; Hana Zuwayid Dulaymi Alanazi,; Anfal Jaber Sarib Alruwaili, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Objective: To explore the experiences and perceptions of surgical patients and nursing technicians regarding the impact of a mindfulness intervention on postoperative pain management and opioid use. Methods: A qualitative descriptive design was used. Semi-structured interviews were conducted with a purposive sample of 20 patients who underwent elective surgery and received a nursing technician-led mindfulness intervention, as well as 10 nursing technicians who delivered the intervention. Interviews were audio-recorded, transcribed verbatim, and analyzed using thematic analysis. Results: Four main themes emerged: (1) "A new way of coping with pain" described how mindfulness helped patients reframe their relationship with pain and develop adaptive coping strategies; (2) "Empowered to take control" captured patients' increased sense of self-efficacy and active engagement in their pain management; (3) "A viable alternative to opioids" reflected patients' and nursing technicians' views of mindfulness as an effective adjunct or alternative to opioid analgesics; and (4) "Challenges and future directions" highlighted barriers, facilitators, and suggestions for improving the accessibility and sustainability of the intervention. Conclusions: Nursing technician-led mindfulness interventions show promise in promoting adaptive pain coping, patient empowerment, and reduced reliance on opioids after surgery. However, additional research is needed to refine intervention protocols, evaluate clinical outcomes, and address implementation barriers. Nursing technicians are well-positioned to integrate mindfulness into postoperative care with appropriate training and organizational support.